2015
DOI: 10.1016/j.fsigss.2015.10.006
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA markers for forensic body fluid identification obtained from miRCURY™ LNA array

Abstract: MicroRNA is a promising marker for forensic body identification especially in compromised samples and mixtures because of its small size and tissue specific expression manner. Previously, five research groups have reported specific miRNAs screened from different arrays for body fluid identification. Our study aims to screen appropriate miRNAs for forensic body fluid identification through Exiqon's miRCURY TM LNA Array. Five samples of six common body fluids were collected including peripheral blood, menstrual … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 6 publications
0
9
0
Order By: Relevance
“…In the last decade, a lot of research has been carried out to identify body fluid origin using miRNAs profiling [ 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 ].…”
Section: Mirna and Body Fluid Identificationmentioning
confidence: 99%
See 1 more Smart Citation
“…In the last decade, a lot of research has been carried out to identify body fluid origin using miRNAs profiling [ 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 ].…”
Section: Mirna and Body Fluid Identificationmentioning
confidence: 99%
“…Microarray platforms highlighted many differentially expressed miRNAs [ 35 , 36 , 37 , 38 ] but qRT PCR is necessary to validate data [ 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 ]. qRT-PCR is the common strategy for miRNA profiling determining the relative differences in expression of various miRNAs.…”
Section: Mirna and Body Fluid Identificationmentioning
confidence: 99%
“…Research has shown that miRNAs have the potential to identify forensically relevant body fluids, where a pair of oligonucleotides can be used to detect a specific miRNA sequence in high abundance in a body fluid. For example, the forensic literature has thus far demonstrated that miR‐891a‐5p is consistently differentially expressed in semen as opposed to other body fluids, while miR‐200b‐3p may be highly expressed in blood more than in other body fluids (). Furthermore, miRNAs let‐7 g and let‐7i are highly conserved among species and have shown similar abundance within and across multiple body fluids, allowing these miRNAs to be used as endogenous reference markers during analysis ().…”
mentioning
confidence: 99%
“…Once matured, these markers extend between 19-25 nucleotide bases long and have long lifetime stabilities due to decreased susceptibility to environmental factors 64 . Several miRNA markers have been proposed for unique identification of body fluids including blood, saliva, and vaginal fluid [64][65][66][67][68][69] .…”
Section: Rna-based Methodsmentioning
confidence: 99%
“…Unfortunately, very few of the markers identified have been verified by multiple studies due to controversial results 65 . For instance, nine markers were identified for peripheral blood, but of these markers, only two, miR-451 and miR-16 were identified in multiple studies 14 .…”
Section: Rna-based Methodsmentioning
confidence: 99%